Going public: the emergence and effects of soft bureaucracy within a knowledge-intensive firm - Robertson, Maxine; Swan, Jacky (2004)
The aim of this paper is to explore and explain the emergence over time of forms of organization and governance (referred to as `organizing templates') in a knowledge-intensive firm (KIF). A longitudinal case study tracks the ways in which this firm has evolved from its inception in 1986 through to 2001. The analysis emphasizes, in particular, the strategic role of power politics in shaping organizing templates following firm success and expansion. The paper focuses on the shift away from adhocracy as the (ideological) organizing template and towards a new form of governance within the firm, characterized as soft bureaucracy. It shows how this shift coincides with economic, technological and cultural imperatives imposed by the increased sovereignty of the market. A multi-level analytical model of organizational change processes is outlined in which shifting dominant management logics are aligned with firm level innovations through organizing templates. This framework is used to structure our narrative historical account of the various phases of restructuring throughout the period. The paper attempts to inform existing understanding of soft bureaucracy by showing how this particular form of governance emerges in a KIF through the interplay between macro-level sectoral change and micro-political processes. It concludes by considering first the implications of this shift for firm level knowledge work processes, and second, the politics of organizational change more generally in the knowledge-intensive sector at the start of the 21st century. - Reproduced.
Keywords: Organizational change; Bureaucracy